Financial sanctions: the European Union’s response to Russia’s assertive foreign policy in Ukraine. - Kociņa, Līva (Riga Graduate School of Law, 2018)
This thesis is focused on the EU imposed financial sanctions as a response to Russia’s aggressive foreign policy in Ukraine (2014-2017). Furthermore, it examines whether financial sanctions have destabilized the status quo authoritarian regime in Russia. The findings of this thesis are of significant importance since Russia is a large trading partner of important raw materials and natural resources for the EU.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Financial sanctions